VD_FINDINFO Jug / 2023 / 3 vom 8. Juni 2022 - VD Tribunal cantonal (2022)
CONFRONTATION, IN DUBIO PRO REO, TENTATIVE SIMPLE, HOMICIDE, INTERNEMENTDROIT PÉNAL | 22 ad 111 CP, 47 CP, 49 al. 1 CP, 64 al. 1 CP, 10 al. 3 CPP (CH), 147 al. 1 CPP (CH)